Systematic evaluation of photodetector performance for plastic scintillation dosimetry. Issue 11 (8th October 2015) - Boivin, Jonathan; Beddar, Sam; Guillemette, Maxime; Beaulieu, Luc
Abstract : Purpose: The authors' objective was to systematically assess the performance of seven photodetectors used in plastic scintillation dosimetry. The authors also propose some guidelines for selecting an appropriate detector for a specific application. Methods: The plastic scintillation detector (PSD) consisted of a 1‐mm diameter, 10‐mm long plastic scintillation fiber (BCF‐60), which was optically coupled to a clear 10‐m long optical fiber of the same diameter. A light‐tight plastic sheath covered both fibers and the scintillator end was sealed. The clear fiber end was connected to one of the following photodetectors: two polychromatic cameras (one with an optical lens and one with a fiber optic taper replacing the lens), a monochromatic camera with an optical lens, a PIN photodiode, an avalanche photodiode (APD), or a photomultiplier tube (PMT). A commercially available W1 PSD was also included in the study, but it relied on its own fiber and scintillator. Each PSD was exposed to both low‐energy beams (120, 180, and 220 kVp) from an orthovoltage unit and high‐energy beams (6 and 23 MV) from a linear accelerator. Various dose rates were tested to identify the operating range and accuracy of each photodetector. Results: For all photodetectors, the relative uncertainty was less than 5% for dose rates higher than 3 mGy/s. The cameras allowed multiple probes to be used simultaneously, but they are less sensitive to low‐light signals. The PIN, APD, and PMT had higher sensitivity, making them more suitable for low dose rate and out‐of‐field dose monitoring. The relative uncertainty of the PMT was less than 1% at the lowest dose rate achieved (0.10 mGy/s), suggesting that it was optimal for use in live dosimetry. Conclusions: For dose rates higher than 3 mGy/s, the PIN diode is the most effective photodetector in terms of performance/cost ratio. For lower dose rates, such as those seen in interventional radiology or high‐gradient radiotherapy, PMTs are the optimal choice.